Book reviews - Zavadskas, Edmundas Kazimieras; Podvezko, Valentinas (Journal of Business Economics and Management, 2008)
DESIGN AND APPLICATION OF INTELLIGENT INFORMATION SYSTEMSReviewed book: Dalé Dzemydiené. Intelektualizuotų informacinių sistemų projektavimas ir taikymas: monografija. Vilnius: Mykolo Romerio universiteto leidybos centras, 2006. 352 p. [Design and Application of Intelligent Information Systems, ISBN: 9955-19-051-5 in Lithuanian].GAME THEORY IN BUILDING TECHNOLOGY AND MANAGEMENTReviewed book: E. K. Zavadskas, F. Peldschus, L. Ustinovičius, Z. Turskis. Lošimų teorija statybos technologijoje ir vadyboje. Vilnius: Technika, 2004 [Game Theory in Building Technology and Management, ISBN: 9986-05-700-0 in Lithuanian].METHODS AND MODELS OF RESEARCH IN CONSTRUCTION PROJECT ENGINEERINGReviewed book: Oleg Kapliński (Eds.). Methody i modele badań w inžynierii przedsięwzięć budowlanych. Polska akademia nauk, komitet inžynierii lądowej i wodnej, Warszawa, 2007 [Methods and Models of Research in Construction Project Engineering, ISBN: 978-83-89687-22-7, ISSN: 0137-5393 in Polish].First published online: 14 Oct 2010